THE CONTENT ANALYSIS OF BAHASA INGGRIS TEXTBOOK USED IN THE FIRST CLASS OF SENIOR HIGHT SCHOOL 1 NAN SABARIS - Johari, Indra; Syaveny, Niza (Universitas PGRI Sumatera Barat, 2022)
This research was based on varieties textbook circulating in learning. The method used in this research is descriptive research method, by analyzing the book